Solution-focused coaching and resilience among unemployed women in the financial services sector in South Africa - Guvi, Rumbidzai Candy Tatenda (My University, 2020)
The outlook for South Africa’s economy remains bleak. The latest economic figures point to a nation that is not only battling a stagnant economy, but one facing low Gross Domestic Product (GDP) growth, potential ratings downgrade, and as a result, increased poverty and inequality. To confront these challenges, companies across the country are turning to restructuring and retrenchments as a way of remaining viable and competitive businesses. The unintended consequences of these actions, however, is an increase in the levels of unemployment. The purpose of this study was to explore how solution-focused coaching can build resilience among women who have become unemployed as a result of companyrelated restructuring and retrenchments from the financial services sector in South Africa. For this mixed methods study, purposeful sampling was chosen. This type of sampling was the most appropriate, given that the demographic profile of this sample would be unemployed women from a multiplicity of organisations across the financial services sector. Over a four month period, three solution-focused groups and one-on-one coaching sessions were conducted for a group of nine (9) unemployed women. The duration of unemployment ranged from between 0 – 12 months. As a result, some of the women in this study were in the process of serving their retrenchment notices. To understand the degree of resilience capacity among these unemployed women, the researcher administered a similar resilience scale questionnaire to all participants, pre- and post- the coaching intervention. The results of this study showed that solution-focused coaching can lead to an improvement in the resilience levels among unemployed women. Prior to the implementation of the coaching intervention, only three (3) women exhibited high levels of resilience. Post the coaching intervention, only one (1) participant out of a total of nine (9) participants, exhibited low levels of resilience capacity. The results of this study also revealed the importance of solution-focused coaching in two ways: (1) highlighting the impact of unemployment on women and (2) positive effects of solution-focused coaching among unemployed women. The women in this study detailed both their psychological and financial struggles as a result of their job losses. However, what is poignant too, is that during and post the coaching intervention, all the participants highlighted the positive effects of solution-focused coaching, including improved levels of resilience capacity, increased confidence, heightened levels of self-awareness, and an intense focus on the potential opportunities in the future. The key message is that South African organisations, with the support of executive coaches, need to do more to support women impacted by unemployment by introducing coaching interventions as part of their restructuring and retrenchment processes. Within this process, there is also a call for organisations to be more empathetic to the impact that restructuring and retrenchments have on their employees.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Management in the field of Business Executive Coaching to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2020
Keywords: Unemployment; Unemployed; Unemployed women; Restructuring; Retrenchment; SDG-8: Decent work and economic growth